Effect of pine cone filler particle size and treatment on the performance of recycled thermoplastics reinforced wood composites. (2022) - Singh, Manoj Kumar; Arora, Gaurav; Tewari, Renu; Zafar, Sunny; Pathak, Himanshu; Sehgal, Anuj Kumar
Abstract: Present research studied the effect of 5% alkali treatment and size of pine cone (Pinus Roxburgii Sargent) on the mechanical performance. Recycled thermoplastic waste and alkali treated pine cone of different size has manufactured using microwave-assisted compression molding (MACM) technique. The MACM technique has used because of inherent benefits of less cost, time and energy consumption while manufacturing the wood composites. To explore the feasibility of uses of wood composites in different applications, mechanical performance i.e., tensile and flexural test were performed. Mechanical tests were employed to examine the influence of pine cone particle size on mechanical performance of the composite. This study revealed that wood composite having treated pine cone filler and fine particle size showed enhanced mechanical performance.